Do ESG Score, Firm Value, and Gender Diversity Enhance Corporate Performance? Evidence from Emerging Asia-Pacific Industrial Firms - Junika Halawa; Ilyona Risty (Universitas Pelita Harapan, 2025)
This study investigates the effect of Environmental, Social, and Governance (ESG) score, firm value, and gender diversity on corporate performance, measured by Return on Assets (ROA), in the industrial sector of emerging Asia-Pacific markets. Using a sample of publicly listed companies, the research aims to provide empirical evidence on how sustainability practices, market valuation, and board diversity contribute to financial performance. ESG scores are applied as a proxy for corporate sustainability, while firm value reflects investors’ perception of growth potential, and gender diversity is considered an indicator of inclusivity in corporate governance. The study employs quantitative analysis to examine the relationships among these variables. The findings are expected to demonstrate whether ESG initiatives and gender diversity complement firm value in driving profitability. This research contributes to the growing literature on sustainable finance by highlighting the role of non-financial factors in shaping firm performance in emerging markets. The results provide insights for managers, policymakers, and investors regarding the strategic importance of ESG and diversity in achieving long-term competitiveness.